2002
DOI: 10.1182/blood.v100.9.3361
|View full text |Cite
|
Sign up to set email alerts
|

Enforced expression of tissue inhibitor of matrix metalloproteinase-3 affects functional capillary morphogenesis and inhibits tumor growth in a murine tumor model

Abstract: Homeostasis of the extracellular matrix is a delicate balance between degradation and remodeling, the balance being maintained by the interaction of activated matrix metalloproteinases (MMPs) and specific tissue inhibitors of matrix metalloproteinases (TIMPs). Up-regulation of MMP activity, favoring proteolytic degradation of the basement membrane and extracellular matrix, has been linked to tumor growth and metastasis, as well as tumor-associated angiogenesis, whereas inhibition of MMP activity appears to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 44 publications
6
78
1
Order By: Relevance
“…Different effects of TIMP3 restoration on tumor cell growth have been reported. No effect on in vitro proliferation of murine neuroblastoma and melanoma cells was observed (Spurbeck et al, 2002); on the contrary, in human melanoma, neuroblastoma and malignant peripheral nerve sheath tumor, TIMP3 was reported to induce apoptosis (Ahonen et al, 2003;Mahller et al, 2008). The lack of effect of TIMP3 on the growth rate of NIM1 cells might be related to their thyroid origin and/or to the advanced tumor stage they represent, being derived from a PTC metastasis.…”
Section: Discussionmentioning
confidence: 91%
“…Different effects of TIMP3 restoration on tumor cell growth have been reported. No effect on in vitro proliferation of murine neuroblastoma and melanoma cells was observed (Spurbeck et al, 2002); on the contrary, in human melanoma, neuroblastoma and malignant peripheral nerve sheath tumor, TIMP3 was reported to induce apoptosis (Ahonen et al, 2003;Mahller et al, 2008). The lack of effect of TIMP3 on the growth rate of NIM1 cells might be related to their thyroid origin and/or to the advanced tumor stage they represent, being derived from a PTC metastasis.…”
Section: Discussionmentioning
confidence: 91%
“…However, TIMPs are multifunctional proteins that in addition to their MMPinhibitory effect also demonstrate distinct tumour-stimulatory functions (Jiang et al, 2002). Experimental studies have shown that TIMP-3 may show activity to inhibit angiogenesis and induce apoptosis (Ahonen et al, 1998;Spurbeck et al, 2002). It has also been published that high TIMP-3 mRNA levels are associated with a good prognosis in breast cancer (Kotzsch et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Retrovirus-mediated expression of TIMP-3 in tumor cells inhib- 145 MMP-2 Various IFN-a 147 EC proliferation/migration Angiostatin 148,149 Various Endostatin 117,150 MT1-MMP, MMP-2 Various Arresten 151 EC proliferation, migration Canstatin 152 EC viability, migration Tumstatin 153,154 EC viability, migration, protein synthesis Platelet factor 4 155 VEGF and bFGF signaling TIMP-1 156 Broad-range Various effects, including MMP inhibition TIMP-2 157 Broad-range Various effects, including MMP inhibition TIMP-3 138 Broad-range Various effects, including MMP inhibition TIMP-4 136 Broad-range Various effects, including MMP inhibition Exogenous/synthetic TNP-470 158 EC proliferation Squalamine 159 EC proliferation Captopril 160 MMP-2, MMP-9 EC migration Combretastatin-A4 161 EC tubulin CP-547, 632 162 VEGFR-2 and bFGF kinases Vitaxin 163 a v b 3 integrin, EC apoptosis EMD121974 164 a v b 3 and a v b 5 integrin COL-3 83 MMP-2, -9, -14 MMPs Neovastat 165,166 MMP-2, -9, -12 MMPs, designed to avoid sheddases BMS-275291 54 MMP-1, -2, -3, -7, -9, -14 Bevacizumab 167 VEGF ited tumor growth and angiogenesis in vivo. Tumors overexpressing TIMP-3 failed to form a functional vasculature and had reduced pericyte recruitment.…”
Section: Timps As Potential Antiangiogenic Agentsmentioning
confidence: 99%
“…Tumors overexpressing TIMP-3 failed to form a functional vasculature and had reduced pericyte recruitment. 138 Intratumoral adenoviral delivery of TIMP-3 (AdTIMP-3) has been shown to inhibit growth of preestablished tumors and also angiogenesis associated with these tumors, even though only a small percentage of tumor cells expressed TIMP-3 after adenoviral administration. This suggests that TIMP-3 expressed by the AdTIMP-3 tumor cells was having a bystander effect on the untransduced tumor cells, illustrating that in the case of gene transfer systems, secreted proteins such as the TIMPs are advantageous as antiangiogenesis/anticancer agents.…”
Section: Timps As Potential Antiangiogenic Agentsmentioning
confidence: 99%